Pembelajaran Bahasa Indonesia Berbasis Kecerdasan Buatan untuk Meningkatkan Literasi Akademik Mahasiswa - Nurfitri Nurfitri (Ameena Journal, 2026)
The development of artificial intelligence has created new opportunities for Indonesian language learning in higher education, particularly in supporting students’ academic literacy. However, its use is often limited to completing academic assignments and has not been fully integrated into a structured, critical, and responsible learning strategy. This study aims to analyze the implementation of artificial intelligence-based Indonesian language learning, its benefits and risks, and its contribution to improving students’ ability to understand, process, evaluate, and produce academic texts. The study employed a library research method by reviewing relevant scholarly articles, books, proceedings, research reports, and academic documents. Data were analyzed through source collection, information classification, critical reading, comparison of findings, synthesis, and conclusion drawing. The findings indicate that artificial intelligence can assist students in understanding text structures, developing ideas, improving linguistic accuracy, strengthening textual coherence, and obtaining immediate feedback. Nevertheless, its use may also create dependence, weaken independent thinking, and encourage students to accept information without adequate verification. Its effectiveness is determined by instructional design, lecturers’ ability to provide guidance, students’ digital literacy, and the reinforcement of academic ethics. This study concludes that artificial intelligence should be positioned as a learning partner rather than a substitute for students’ intellectual processes. The study contributes to the field by providing a conceptual foundation for developing adaptive, critical, and responsible artificial intelligence-based Indonesian language learning that strengthens students’ academic literacy.